Catalytic Direct Nucleophilic Substitution of Primary Morita–Baylis–Hillman Adducts and Application to the Straightforward Synthesis of Dihydroisoindolones - Ayadi, Marwa; Mpawenayo, Pierre C.; Rezgui, Farhat; Leclerc, Eric; Vrancken, Emmanuel; Campagne, Jean-Marc (Synthesis, 2018)
An interesting γ-carbonyl effect permits the dual iron/boron-catalyzed direct nucleophilic substitution of functionalized primary allylic alcohols with a large variety of nucleophiles. The resulting substitution products are useful synthetic platforms for heterocycle synthesis, as illustrated in a ready access to tetrahydroisoindol-4-ones.
Keywords: iron catalysis; boron catalysis; dual catalysis; isoindolones; nucleophilic substitution; neighboring group participation